# The sum of intercepts to the tangents to the curve \[\sqrt x + \sqrt y = \sqrt a \] upon the coordinate axes is

A. \[2a\]

B. \[a\]

C. \[2\sqrt 2 a\]

D. None of these

Last updated date: 25th Mar 2023

•

Total views: 306.3k

•

Views today: 7.84k

Answer

Verified

306.3k+ views

Hint: Consider any point on the given curve and find the tangent to the curve at the considered point. Then take out the intercepts to the obtained tangent and add them, which gives the required solution.

Complete step-by-step answer:

Let \[P\left( {{x_1},{y_1}} \right)\] be a point on the curve \[\sqrt x + \sqrt y = \sqrt a \]

Then, \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a .................................\left( i \right)\]

Now, differentiating the curve \[\sqrt x + \sqrt y = \sqrt a \], we have

\[

\Rightarrow \dfrac{{d\left( {\sqrt x } \right)}}{{dx}} + \dfrac{{d\left( {\sqrt y } \right)}}{{dx}} = \dfrac{{d\left( {\sqrt a } \right)}}{{dx}} \\

\Rightarrow \dfrac{1}{{2\sqrt x }} + \dfrac{1}{{2\sqrt y }}\dfrac{{dy}}{{dx}} = 0 \\

\Rightarrow \dfrac{{dy}}{{dx}} = - \dfrac{{\sqrt y }}{{\sqrt x }} \\

\]

So, the slope of the tangent at \[P\left( {{x_1},{y_1}} \right)\] to the curve \[\sqrt x + \sqrt y = \sqrt a \] is

\[{\left( {\dfrac{{dy}}{{dx}}} \right)_P} = - \dfrac{{\sqrt {{y_1}} }}{{\sqrt {{x_1}} }}\]

The equation of the tangent at \[P\left( {{x_1},{y_1}} \right)\] to the curve \[\sqrt x + \sqrt y = \sqrt a \] is

\[

y - {y_1} = {\left( {\dfrac{{dy}}{{dx}}} \right)_P}\left( {x - {x_1}} \right) \\

\Rightarrow y - {y_1} = - \dfrac{{\sqrt {{y_1}} }}{{\sqrt {{x_1}} }}\left( {x - {x_1}} \right) \\

\Rightarrow \left( {y - {y_1}} \right)\sqrt {{x_1}} = - \sqrt {{y_1}} \left( {x - {x_1}} \right) \\

\Rightarrow y\sqrt {{x_1}} - {y_1}\sqrt {{x_1}} = - x\sqrt {{y_1}} + {x_1}\sqrt {{y_1}} \\

\Rightarrow x\sqrt {{y_1}} + y\sqrt {{x_1}} = {x_1}\sqrt {{y_1}} + {y_1}\sqrt {{x_1}} \\

\]

Dividing both sides with \[\sqrt {{x_1}} \sqrt {{y_1}} \] we have

\[ \Rightarrow \dfrac{x}{{\sqrt {{x_1}} }} + \dfrac{y}{{\sqrt {{y_1}} }} = \sqrt {{x_1}} + \sqrt {{y_1}} \]

Since, \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a \]

\[

\Rightarrow \dfrac{x}{{\sqrt {{x_1}} }} + \dfrac{y}{{\sqrt {{y_1}} }} = \sqrt a \\

\Rightarrow \dfrac{x}{{\sqrt a \sqrt {{x_1}} }} + \dfrac{y}{{\sqrt a \sqrt {{y_1}} }} = 1 \\

\Rightarrow \dfrac{x}{{\sqrt {a{x_1}} }} + \dfrac{y}{{\sqrt {a{y_1}} }} = 1 \\

\]

We know that if \[\dfrac{x}{a} + \dfrac{y}{b} = 1\] is the equation of the line, then the intercepts upon the coordinate axes is \[a{\text{ and }}b\].

So, the intercepts of the formed tangent \[\dfrac{x}{{\sqrt {a{x_1}} }} + \dfrac{y}{{\sqrt {a{y_1}} }} = 1\] is \[\sqrt {a{x_1}} {\text{ and }}\sqrt {a{y_1}} \].

Therefore, the sum of the intercepts is

\[

\Rightarrow \sqrt {a{x_1}} + \sqrt {a{y_1}} \\

\Rightarrow \sqrt a \left( {\sqrt {{x_1}} + \sqrt {{y_1}} } \right) \\

\]

Since, we have \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a \]

\[

\Rightarrow \sqrt a \left( {\sqrt a } \right) \\

\Rightarrow a \\

\]

Therefore, the sum of the intercepts of the curve \[\sqrt x + \sqrt y = \sqrt a \] upon the coordinate axes is \[a\].

Thus, the correct option is B. \[a\]

Note: Here the tangent must touch both the coordinate axes to form intercepts. In the given above formula \[a\] is the length of \[x\] axis intercept and \[b\] is the length of \[y\] axis intercept.

Complete step-by-step answer:

Let \[P\left( {{x_1},{y_1}} \right)\] be a point on the curve \[\sqrt x + \sqrt y = \sqrt a \]

Then, \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a .................................\left( i \right)\]

Now, differentiating the curve \[\sqrt x + \sqrt y = \sqrt a \], we have

\[

\Rightarrow \dfrac{{d\left( {\sqrt x } \right)}}{{dx}} + \dfrac{{d\left( {\sqrt y } \right)}}{{dx}} = \dfrac{{d\left( {\sqrt a } \right)}}{{dx}} \\

\Rightarrow \dfrac{1}{{2\sqrt x }} + \dfrac{1}{{2\sqrt y }}\dfrac{{dy}}{{dx}} = 0 \\

\Rightarrow \dfrac{{dy}}{{dx}} = - \dfrac{{\sqrt y }}{{\sqrt x }} \\

\]

So, the slope of the tangent at \[P\left( {{x_1},{y_1}} \right)\] to the curve \[\sqrt x + \sqrt y = \sqrt a \] is

\[{\left( {\dfrac{{dy}}{{dx}}} \right)_P} = - \dfrac{{\sqrt {{y_1}} }}{{\sqrt {{x_1}} }}\]

The equation of the tangent at \[P\left( {{x_1},{y_1}} \right)\] to the curve \[\sqrt x + \sqrt y = \sqrt a \] is

\[

y - {y_1} = {\left( {\dfrac{{dy}}{{dx}}} \right)_P}\left( {x - {x_1}} \right) \\

\Rightarrow y - {y_1} = - \dfrac{{\sqrt {{y_1}} }}{{\sqrt {{x_1}} }}\left( {x - {x_1}} \right) \\

\Rightarrow \left( {y - {y_1}} \right)\sqrt {{x_1}} = - \sqrt {{y_1}} \left( {x - {x_1}} \right) \\

\Rightarrow y\sqrt {{x_1}} - {y_1}\sqrt {{x_1}} = - x\sqrt {{y_1}} + {x_1}\sqrt {{y_1}} \\

\Rightarrow x\sqrt {{y_1}} + y\sqrt {{x_1}} = {x_1}\sqrt {{y_1}} + {y_1}\sqrt {{x_1}} \\

\]

Dividing both sides with \[\sqrt {{x_1}} \sqrt {{y_1}} \] we have

\[ \Rightarrow \dfrac{x}{{\sqrt {{x_1}} }} + \dfrac{y}{{\sqrt {{y_1}} }} = \sqrt {{x_1}} + \sqrt {{y_1}} \]

Since, \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a \]

\[

\Rightarrow \dfrac{x}{{\sqrt {{x_1}} }} + \dfrac{y}{{\sqrt {{y_1}} }} = \sqrt a \\

\Rightarrow \dfrac{x}{{\sqrt a \sqrt {{x_1}} }} + \dfrac{y}{{\sqrt a \sqrt {{y_1}} }} = 1 \\

\Rightarrow \dfrac{x}{{\sqrt {a{x_1}} }} + \dfrac{y}{{\sqrt {a{y_1}} }} = 1 \\

\]

We know that if \[\dfrac{x}{a} + \dfrac{y}{b} = 1\] is the equation of the line, then the intercepts upon the coordinate axes is \[a{\text{ and }}b\].

So, the intercepts of the formed tangent \[\dfrac{x}{{\sqrt {a{x_1}} }} + \dfrac{y}{{\sqrt {a{y_1}} }} = 1\] is \[\sqrt {a{x_1}} {\text{ and }}\sqrt {a{y_1}} \].

Therefore, the sum of the intercepts is

\[

\Rightarrow \sqrt {a{x_1}} + \sqrt {a{y_1}} \\

\Rightarrow \sqrt a \left( {\sqrt {{x_1}} + \sqrt {{y_1}} } \right) \\

\]

Since, we have \[\sqrt {{x_1}} + \sqrt {{y_1}} = \sqrt a \]

\[

\Rightarrow \sqrt a \left( {\sqrt a } \right) \\

\Rightarrow a \\

\]

Therefore, the sum of the intercepts of the curve \[\sqrt x + \sqrt y = \sqrt a \] upon the coordinate axes is \[a\].

Thus, the correct option is B. \[a\]

Note: Here the tangent must touch both the coordinate axes to form intercepts. In the given above formula \[a\] is the length of \[x\] axis intercept and \[b\] is the length of \[y\] axis intercept.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Write a letter to the Principal of your school to plead class 10 english CBSE